Hemosiderin-laden macrophages are an independent factor correlated with pulmonary vascular resistance in idiopathic pulmonary fibrosis: a case control study. Issue 1 (December 2017) - Fukihara, Jun; Taniguchi, Hiroyuki; Ando, Masahiko; Kondoh, Yasuhiro; Kimura, Tomoki; Kataoka, Kensuke; Furukawa, Taiki; Johkoh, Takeshi; Fukuoka, Junya; Sakamoto, Koji; Hasegawa, Yoshinori
Abstract Background Increases in hemosiderin-laden macrophages (HLM) are reported to be observed in idiopathic pulmonary fibrosis (IPF). According to a recent study, significant correlation between hemosiderin deposition in the lung tissue of IPF and pulmonary hypertension evaluated by echocardiography has been suspected. In this study, we aimed to evaluate whether HLM in bronchoalveolar lavage fluid (BALF) is a factor correlated with pulmonary hemodynamic parameters evaluated by right heart catheterization in patients with IPF. Methods Initial data from 103 consecutive patients with IPF who underwent surgical lung biopsy between November 2007 and March 2014 were retrospectively analyzed. The "HLM score" of BALF was established by dividing the number of Perls' Prussian blue stain positive macrophages by the total number of macrophages counted. Results BALF showed an elevated HLM score (38.2%). Right heart catheterization revealed mean pulmonary arterial pressure (mPAP) of 16.3 mmHg and pulmonary vascular resistance (PVR) of 1.55 Wood units. HLM score was positively correlated with mPAP (ρ = 0.204;p  = 0.038) and PVR (ρ = 0.349, p  < 0.001). In multivariate analysis, 6-min walk distance (standardized partial regression coefficient [β], −0.391;p  < 0.001), minimum oxygen saturation during 6-min walk distance (β, −0.294;p  = 0.001) and HLM score (β, 0.265;p  = 0.002) were independently correlated with PVR. Conclusions HLM score in BALF is an independent factor correlated with PVR in patients with IPF.